Estimating Hydrogen Bond Energy in Integral Membrane Chromoproteins by High Hydrostatic Pressure Optical Spectroscopy - Kangur, Liina; Olsen, John D.; Hunter, C. Neil; Freiberg, Arvi (IntechOpen, 2012)
None